2021
DOI: 10.3390/plants10061051
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Sumac PlantCrystals: Influence of High-Pressure Homogenization on Antioxidant Activity of Sumac (Rhus coriaria L.)

Abstract: Oxidative stress diseases are usually treated or prevented by using antioxidants from natural or artificial sources. However, as a sustainable source of phytochemicals, plants got a renewed interest in obtaining their active agents using green extraction technologies, i.e., sustainable extraction techniques that reduce energy consumption, use renewable sources and result in less post-extraction wastes. The high-pressure homogenization (HPH) technique was introduced into the food industry since it was invented … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The results of our study, highlighting the higher activity of the methanol extract, are therefore in line with previous comparative studies that showed that methanolic extracts of sumac contain a higher content of flavonoids and phenolics when compared with other extracts [ 13 , 14 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The results of our study, highlighting the higher activity of the methanol extract, are therefore in line with previous comparative studies that showed that methanolic extracts of sumac contain a higher content of flavonoids and phenolics when compared with other extracts [ 13 , 14 ].…”
Section: Resultssupporting
confidence: 93%
“…Recently, sumac has gained more attention due to its high amount of polyphenols. Numerous studies have been conducted to study the in vitro antimicrobial effectiveness of Rhus coriaria extracts against several bacterial species [ 14 , 35 , 36 ], while limited data are available on their effect against MDR bacteria. In this study, the antibacterial activity of Rhus coriaria extracts was tested against five MDR Enterobacteriaceae isolates, S. aureus ATCC 6538, and E. coli ATCC 25922.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulating plants allows one to prevent the occurrence of harmful cellular mechanisms, hence the great interest in obtaining plant extracts with high biological activity. An important aspect is also the use of efficient and environmentally friendly extraction technologies [ 97 , 98 ]. However, it is also important to establish a critical value at which the effect of an action will negatively affect a given plant.…”
Section: Resultsmentioning
confidence: 99%